Du carbon lock-in au nuclear lock-in : les verrous spatiaux aux changements de politique nucléaire en Suède - Teva Meyer (Développement Durable et Territoires)
Energy geographers have shown that the difficulty encountered by modern societies to decrease their fossil fuel consumption could be explained by the influence of spatial path dependencies, also called carbon lock-in. This article tests the relevance of this approach to the analysis of continuity in nuclear policies. The article focuses on Sweden, where, despite a nuclear phase-out decision taken in 1980, nuclear power still produces approximately half of the country’s electricity. Relying on interviews with pro-nuclear actors, this study shows that the permanence of nuclear policy in Sweden can be explained by the existence of a nuclear lock-in. These path dependencies are constituted by the material features of the energy system – elements upon which the involved political actors project their own values and norms, and, either unconsciously of strategically, mobilize spatial representations.